LEXICAL AND GRAMMATICAL FEATURES OF THE TRANSLATION OF IT TERMS (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER'S THEORY, 2024)
Translating IT terms requires a deep understanding of both the source and target languages, as well as familiarity with IT concepts and terminology. Balancing lexical accuracy with grammatical correctness ensures that the translated text effectively communicates technical information to its audience in the target language. In this model of article, we will see how these features are learned, what kind of issues we can overcome, and both grammatical and lexical features are discussed. By mastering both lexical and grammatical features of translating IT terminologies, translators can effectively bridge language barriers in the dynamic and ever-evolving landscape of technology.